2023
DOI: 10.3390/life13081683
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Microgravity-Induced Changes to Drug Response in Cancer Cells Quantified Using Fluorescence Morphometry

Abstract: Unlike plants that have special gravity-sensing cells, such special cells in animals are yet to be discovered. However, microgravity, the condition of apparent weightlessness, causes bone, muscular and immune system dysfunctions in astronauts following spaceflights. Decades of investigations show correlations between these organ and system-level dysfunctions with changes induced at the cellular level both by simulated microgravity as well as microgravity conditions in outer space. Changes in single bone, muscl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…However, fluorescence-guided morphometry independent of the MMM was performed using a Zeiss Vert.A1 AXIO fluorescence microscope (Carl Zeiss, Jena, Germany) equipped with red, green and blue filters and with an inserted USB microscope camera (AmScope MU300, Ningbo, China), along with its AmScope (86x) image capture program. Details of the advanced fluorometric morphometry performed which yielded information on cytoplasmic cross section and nuclear cross section, following chemotherapeutic interventions, can be found in our recent publications [ 57 , 58 ]. Briefly, the fluorescent dyes Hoechst 33342 (ThermoFisher Scientific, Waltham, MA, USA), at a 0.1 mM final concentration, and Calcein AM (Invitrogen by ThermoFisher Scientific, Waltham, MA, USA), at a final concentration of 1 µg/mL, were used to stain the nucleus and the cytoplasm, respectively, for imaging.…”
Section: Methodsmentioning
confidence: 99%
“…However, fluorescence-guided morphometry independent of the MMM was performed using a Zeiss Vert.A1 AXIO fluorescence microscope (Carl Zeiss, Jena, Germany) equipped with red, green and blue filters and with an inserted USB microscope camera (AmScope MU300, Ningbo, China), along with its AmScope (86x) image capture program. Details of the advanced fluorometric morphometry performed which yielded information on cytoplasmic cross section and nuclear cross section, following chemotherapeutic interventions, can be found in our recent publications [ 57 , 58 ]. Briefly, the fluorescent dyes Hoechst 33342 (ThermoFisher Scientific, Waltham, MA, USA), at a 0.1 mM final concentration, and Calcein AM (Invitrogen by ThermoFisher Scientific, Waltham, MA, USA), at a final concentration of 1 µg/mL, were used to stain the nucleus and the cytoplasm, respectively, for imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has been observed that µg can change the way chemotherapy drugs work. However, there have been limited r-µg studies or animal experiments in space, while most research was conducted on cell culture lines under s-µg conditions [93,94]. Tumor diseases remain the most significant global challenges and, despite scientific advancements in medicine, no conclusive methods have been discovered to prevent tumor development or guide its treatment.…”
Section: Hematological Malignanciesmentioning
confidence: 99%